Fantastic Four : a plague of one - Yoshida, Akira (Fantastic Four series, 2007)
The superhero team of Mr. Fantastic, the Invisible Woman, the Human Torch, and the Thing, work together to stop the evil insectoid Annihilus's rampage. Presented in graphic novel form.